Bioethics in odontology’s curricular net - Guerra, Rina Ana (Acta Bioethica, 2006)
This paper’s purpose is to explore the present state of bioethics as a subject in odontologists’ training curriculum in Argentina. It also shows the graduate’s profile and his needs according to techno-scientific, social and cultural requirements that justify the inclusion of bioethics in the university’s curriculum. Similarly, it draws attention upon the need of a space for bioethics, the so-called science of the new millennium.